FUNGSI SENI KUDA LUMPING BAGI MASYARAKAT JAWA DI DESA SEMINAI KECAMATAN KERINCI KANAN KABUPATEN SIAK - Sri Heni Pawarti Budianingsih; M Razif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Kuda Lumping is one of the entertainment community of Java that has been handed down from ancestors. Kuda lumping is a traditional art that is used for a popular entertainment that is often held in the village Seminai. The intent of Kuda Lumping forged art as entertainment, education, medicine and clean village, adaptation, goal attainment, integration and latent. The objective of this art is to provide entertainment for the villagers Seminai, education, medicine and clean village. Involved in art of Kuda Lumping is public figures, Kuda Lumping handler, Kuda Lumping players Seminai village communities. Being the problem is : what function art of Kuda Lumping for the people in the village Seminai ? What is the meanings contained in art of Kuda Lumping ? This study aims to determine what is the function of art of Kuda Lumping for the people in the village Seminai. To find out the meanings of what is contained in Kuda Lumping. The theory used in this study is the structural functional theory. While the method used was descriptive quantitative, using census and observation techniques. The number of respondents in this study as many as 33 people. Based on the research results of almost all respondents were happy with their art of Kuda Lumping in Seminai village, in addition to entertainment arts is also a positive impact on the community in the village of Java Seminai. Art of Kuda Lumping is also a lot in the favorite by all people, both among parents and adolescents and children. Information about the function of art of Kuda Lumping for the Java community in Seminai can directly from respondents who live in rural sub-district Seminai Kerinci Kanan district Siak. Keywords : Kuda Lumping, Java Community and A-G-I-L Function